Changes in the rural habitat. Chascomús topographic maps, 1826 - 1854 - Aliata, Fernando (Centro de Historia Argentina y Americana, 2010)
The current paper aims to expose territorial organization new strategies on the Buenos Airesï rural area that were materialized during the earlier nineteenth century, and its influence on the urban and social structure of the mentioned zone. In previous researches we postulated that these strategies were which defined, among other aspects, the spatial transformation of this territory, based in three premises: the consolidation of existing villages, the foundation of new ones and the ejidal colonization development. In order to deepen the knowledge of these strategies, Chascomús urban space was analized at two different times of its consolidation: 1826 and 1855. The dates are correspondent with two documents whose spatially represents this site: Saubidet and Arrufó plans. Based on these documents, we aim to define the government strategies concerning to spatial structure, village's consolidation, social structure, so as remark differences among two mentioned times, considering that the first phase is correspondent with frontier expansion, and the second one, with the growth of the pastoral age, with Chascomús as one of the most important centers.